Comparative Analysis of Unemployment Rates in The United States and China During COVID-19 - Bartosz KOZICKI; Marek KALWASIŃSKI (Communications of International Proceedings, 2021)
The paper utilizes the comparative analysis of unemployment rates in the United States and China. The obtained primary data on unemployment rates in various time intervals were compiled on categorized line charts by assigning / subordinating to the considered time series separate scales on additional X and Y axes - in order to detect the regularities governing the given phenomena. Due to the largest increase in the unemployment rate in the history of the United States during the COVID-19 pandemic, 51 states were subject to the study. The analyzes used constant-base dynamics indicators. The study ends with a summary and conclusions.
Keywords: unemployment; unemployment rates in the USA; multivariate analyzes; economic security.